Solar Photovoltaic Generators with MPPT and Battery Storage in Microgrids - B V Rajanna; SVNL Lalitha; Ganta Joga Rao; S K Shrivastava (Institute of Advanced Engineering and Science, 2016)
Maximum power point tracking (MPPT) of a photo voltaic system with different temperature and insolation conditions used for Micro grids can be explained in this paper. The different steps of the design of this controller are presented together with its simulation and the feasibility of control methods to be adopted for the operation of a micro grid when it becomes isolated. Normally, the micro grid operates in interconnected mode with the medium voltage network; however, scheduled or forced isolation can take place. In such conditions, the micro grid must have the ability to operate stably and autonomously. An evaluation of the need of storage devices and load to take off strategies is included in this paper. Solar photovoltaic (PV) energy has witnessed double-digit growth in the past decade. The penetration of PV systems as distributed generators in low-voltage grids has also seen significant attention. In addition, the need for higher overall grid efficiency and reliability has boosted the interest in the microgrid concept. High-efficiency PV-based microgrids require maximum power point tracking (MPPT) controllers to maximize the harvested energy due to the nonlinearity in PV module characteristics. This paper proposes an approach of coordinated and integrated control of solar PV generators with the maximum power point tracking (MPPT) control and battery storage control to provide voltage and frequency (V-f) support to an islanded microgrid. The simulation studies are carried out with the IEEE 13-bus feeder test system in grid connected and islanded microgrid modes. The MPPT of a Photovoltaic System for Micro Grid operation is successfully designed and simulated by using MATLAB/Simulink Software in this paper.